Good morning Hanoi : A year on the airwaves in the new Vietnam - Finlay, Iain (Griffin Press, 2006)
Returning once again to Viet Nam, where more than thirty years previously they had been correspondents during the Vietnam War, Iain Finlay and Trish Clark take up the job of coaching a team of young Vietnamese people at the Voice of Vietnam radio network in Hanoi. Here, Iain and Trish describe their experiences and their encounters with the New Viet Nam. They describe with warmth and humor the various people they work with, and the personalities they meet and get to know in and around the small courtyard where they live. This is a warm, fascinating book about modern Viet Nam, as revealed through the lives of ordinary people.